Current Problems in 2D Numerical Modelling of Water Flow in the River Channels - Grmelová, Eliška; Skokan, Jiří; Juriga, Jan; Chrástová, Veronika; Pospíšilík, Šimon (Vysoké učení technické v Brně,Fakulta stavební, 2024)
Currently, the use of two-dimensional numerical models in modelling water flow in river channels and floodplains is quite common. The quality of hydraulic calculation results is influenced by the number of input parameters. However, crucial in this context is primarily the availability of calibration data. Commonly used data from historical flood records are often burdened with significant uncertainties and, in many cases, are completely lacking. One option to ensure suitable calibration data is to measure flow rates and velocity fields in selected calibration profiles, e.g., using the ADCP method (Acoustic Doppler Current Profiler). The presented article showcases the authors' experiences with the calibration of a 2D numerical model applied to a real location, specifically using the mentioned method. The focus of the calibration lies mainly in the values of Manning’s roughness coefficients and parameters of turbulent models. The conclusion of the article includes a discussion of the results and recommendations for further research directions in the field, which appear promising for practical applications.
Keywords: 2D model; flood; calibration; floodplain; river channel; ADCP